Clear and Distinct Perception in the Stoics, Augustine, and William of Ockham. (31st May 2022) - Nawar, Tamer
Abstract: There is a long history of philosophers granting a privileged epistemic status to cognition of directly present objects. In this paper, I examine three important historic accounts which provide different models of this cognitive state and its connection with its objects: that of the Stoics, who are corporealists and think that ordinary perception may have an epistemically privileged status, but who seem to struggle to accommodate non-perceptual cognizance; that of Augustine, who thinks that incorporeal objects are directly present to us in 'intellectual perception', and that, by way of contrast, ordinary sense-perception does not have a privileged epistemic status; and that of William of Ockham, who allows for unmediated action at a distance and is fairly generous about what counts as being directly present.